2020
DOI: 10.1007/s00134-020-06024-3
|View full text |Cite
|
Sign up to set email alerts
|

Time to intra-arrest therapeutic hypothermia in out-of-hospital cardiac arrest patients and its association with neurologic outcome: a propensity matched sub-analysis of the PRINCESS trial

Abstract: Purpose: To study the association between early initiation of intra-arrest therapeutic hypothermia and neurologic outcome in out-of-hospital cardiac arrest. Methods:A prespecified sub-analysis of the PRINCESS trial (NCT01400373) that randomized 677 bystanderwitnessed cardiac arrests to transnasal evaporative intra-arrest cooling initiated by emergency medical services or cooling started after hospital arrival. Early cooling (intervention) was defined as intra-arrest cooling initiated < 20 min from collapse (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Both trials reported no significant benefits on patient outcomes, although in the latter trial a post hoc analysis of the subgroup of patients with an initial shockable rhythm and in whom cooling was initiated < 20 min from collapse showed improved neurological outcome at 90 days. 226,227 [ 2 4 _ T D $ D I F F ] Optimal target temperature during hypothermia [ 2 0 _ T D $ D I F F ] The Targeted Temperature Management after Cardiac Arrest trial (TTM-trial) randomised 950 OHCA patients with both initial shockable and non-shockable rhythms to a strategy including 36 h of temperature control (i.e. 28 h at target temperature followed by slow rewarming) and fever control up to 72 h after randomisation; the two target temperatures during the intervention phase were 33 C or 36 C. 27 Strict protocols were followed for assessing prognosis and for withdrawal of life-sustaining treatment (WLST).…”
Section: Treatment Of Fevermentioning
confidence: 99%
“…Both trials reported no significant benefits on patient outcomes, although in the latter trial a post hoc analysis of the subgroup of patients with an initial shockable rhythm and in whom cooling was initiated < 20 min from collapse showed improved neurological outcome at 90 days. 226,227 [ 2 4 _ T D $ D I F F ] Optimal target temperature during hypothermia [ 2 0 _ T D $ D I F F ] The Targeted Temperature Management after Cardiac Arrest trial (TTM-trial) randomised 950 OHCA patients with both initial shockable and non-shockable rhythms to a strategy including 36 h of temperature control (i.e. 28 h at target temperature followed by slow rewarming) and fever control up to 72 h after randomisation; the two target temperatures during the intervention phase were 33 C or 36 C. 27 Strict protocols were followed for assessing prognosis and for withdrawal of life-sustaining treatment (WLST).…”
Section: Treatment Of Fevermentioning
confidence: 99%
“…A recent large multicenter RCT confirmed that prehospital transnasal evaporative intra-arrest cooling did not improve the 90-day survival rate and neurologic outcomes of patients with OHCA compared with routine cooling after admission [60,61]. Although evidence supporting the benefit of starting prehospital TH before ROSC is lacking, this method is safe and facilitates the application of TTM in hospitals [62].…”
Section: Timing Of Th Initiationmentioning
confidence: 99%
“…Another approach is that of intranasal cooling, which leads to heat exchange by direct heat loss to air and evaporation of water, which can reach up to a 10% rate of total body heat loss in normal conditions ( 107 ). Transnasal evaporative cooling has been shown to improve neurological outcomes in patients who received cardiopulmonary resuscitation after cardiac arrest with acceptable feasibility and safety ( 112 , 113 ). However, non-invasive cooling using surface cooling and nasopharyngeal cooling is relatively less effective in lowering temperature of the brain parenchyma ( 20 ).…”
Section: Clinical Challenges Of Therapeutic Hypothermia For Acute Isc...mentioning
confidence: 99%